2019
DOI: 10.1017/s1743923x18000892
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Gap in Political Discussion Group Attendance

Abstract: Although women and men enjoy formally equal political rights in today's democracies, there are ongoing gaps in the extent to which they make use of these rights, with women underrepresented in many political practices. The gender gap in democratic participation is problematic because gendered asymmetries in participation entail collective outcomes that are less attentive to women's needs, interests, and preferences. Existing studies consider gender gaps in voting behavior and in certain forms of nonelectoral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Additionally, we see that there is a large difference between the most frequently quoted category and the second most frequently quoted. For men, number 1 is politicians (103,378) and number 2 is sports figures (10,723). For women, politicians are also at the top (29,007), with health professionals second to politicians (9,217).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we see that there is a large difference between the most frequently quoted category and the second most frequently quoted. For men, number 1 is politicians (103,378) and number 2 is sports figures (10,723). For women, politicians are also at the top (29,007), with health professionals second to politicians (9,217).…”
Section: Plos Onementioning
confidence: 99%
“…The underrepresentation of women is pervasive in most areas of society, from elected representatives [ 2 – 5 ] and executives [ 3 , 6 , 7 ] to presidents and faculty in universities [ 5 , 8 , 9 ]. Women are also underrepresented in political discussion groups [ 10 ]. It is, therefore, not entirely surprising that news stories mostly discuss and quote men: Many news stories discuss politicians and business executives, drawing on expert opinion from university professors to do so.…”
Section: Introduction: the Gender Gap In Media And In Societymentioning
confidence: 99%
“…For instance, research shows that young women are less likely than young men to envision themselves running for office and that this impacts their political behavior as adults (Fox and Lawless 2011, 2014). Not only do women self-exclude themselves from electoral politics, women are less likely to participate in discursive practices in the public sphere (Beauvais 2019). Even when disempowered group members participate in politics, the internalized sense that women, the working class, and people of color are “out of their league” in political activity might mean others are more likely to dismiss or ignore disempowered group members’ contributions.…”
Section: Equality Inclusion and Democratic Politicsmentioning
confidence: 99%
“…A review of the literature on small-group discussions shows that women political science students participate less in class discussions (Yaylaci and Beauvais 2017), that women are less likely to participate in group discussions in the public sphere (Beauvais 2019), and women attending group discussions often feel less influential when they do speak (Mendelberg 2002). Continuing with my example of women’s political participation, the legacy of women’s political exclusion embedded in cognitive schemes of perception and appreciation can lead women to perceive themselves (and lead others to perceive them) as less knowledgeable and influential in political conversations.…”
Section: Equality Inclusion and Democratic Politicsmentioning
confidence: 99%
“…Nevertheless, involving politicians in deliberation can increase the likelihood for events to be taken more seriously and reduce the distance between citizens and representatives (Setälä 2017;Farrell et al 2020). Moreover, studies have shown indications of a gender gap in deliberation, adding to worries about deliberation not fulfilling ideals of political equality (Beauvais 2020;Mendelberg, Karpowitz, and Oliphant 2014). For example, women are less willing to participate in deliberation (Karjalainen and Rapeli 2015), and when they do, they tend to speak significantly less than men do (Karpowitz, Mendelberg, and Shaker 2012).…”
Section: Introductionmentioning
confidence: 99%